MANAJEMEN KEPEMIMPINAN DI PONDOK PESANTREN MINHAJ SHAHABAH TAMANSARI BOGOR - Mufid Mufid; Maemunah Sadiyah; Abdul Hayyie Al Kattani (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2023)
As one of the main factors in education and even as an indicator of its success, educational leadership must be managed properly and optimally. Namely through management processes related to the flow or activities of planning, organizing, implementing or acting, and evaluating. This research is a type of field qualitative research located at Mah’had Minhaj Shahabah Tamansari Bogor in 2022 year, focusing on leadership management that is carried out and becomes the main typology in leadership. Based on this research, it can be concluded that the leadership management typology of Mudir Mah’had Minhaj Shahabah Tamansari Bogor is democratic and situational leadership which is framed by prophetic leadership which is the hallmark of leadership in Islamic boarding schools (ma'had). The leadership management has been running effectively and efficiently, but it must continue to be developed continuously, especially in carrying out the vision, mission, and goals of Ma'had that have been set.